Co to jest p (2), jeśli p (x) = x ^ {4} + 3x ^ {3} - 6x ^ {2} - 8x?

Co to jest p (2), jeśli p (x) = x ^ {4} + 3x ^ {3} - 6x ^ {2} - 8x?
Anonim

Odpowiedź:

Zobacz proces rozwiązania poniżej:

Wyjaśnienie:

Znaleźć #p (2) # zastąpić #color (czerwony) (2) # za każde wystąpienie #color (czerwony) (x) # w funkcji #p (x) # i oblicz wynik:

#p (kolor (czerwony) (x)) = kolor (czerwony) (x) ^ 4 + 3 kolor (czerwony) (x) ^ 3 - 6 kolor (czerwony) (x) ^ 2 - 8 kolor (czerwony) (x) # staje się:

#p (kolor (czerwony) (2)) = kolor (czerwony) (2) ^ 4 + (3 * kolor (czerwony) (2) ^ 3) - (6 * kolor (czerwony) (2) ^ 2) - (8 * kolor (czerwony) (2)) #

#p (kolor (czerwony) (2)) = 16 + (3 * 8) - (6 * 4) - 16 #

#p (kolor (czerwony) (2)) = 16 + 24 - 24 - 16 #

#p (kolor (czerwony) (2)) = 0 #